Source‐To‐Sink Aeolian Fluxes From Arid Landscape Dynamics in the Lut Desert. Issue 4 (23rd February 2022) - Chanteloube, Colin; Barrier, Laurie; Derakhshani, Reza; Gadal, Cyril; Braucher, Régis; Payet, Vincent; Léanni, Laëtitia; Narteau, Clément
Abstract: We analyze major landforms of the Lut Desert in Iran to provide a comprehensive source‐to‐sink picture of aeolian systems on time scales from decades to millions of years. We map the modern sandflows, along which we evaluate the volume and chronology associated with the excavation of mega‐yardangs upwind and the formation of giant dunes downwind. Sediment discharges deduced from long‐term erosion and deposition are of the same order of magnitude (10 5 –10 6 m 3 yr −1 ) as short‐term and medium‐term sand discharges derived from wind data and dune morphodynamics. At the scale of the internal aeolian sediment‐routing system of the Lut, we establish an overall sediment budget constrained by the joint development of the erosional and depositional landforms. Our findings thus quantify the geomorphic controls of aeolian processes on arid landscapes at multiple length and time scales, while providing information on mass exchanges between continents and atmosphere. Plain Language Summary: Wind‐blown sand and dust emissions shape singular landscapes in arid environments and globally impact climate, life, and human activities. Nevertheless, the contributions of aeolian processes to the evolution of continental surfaces and to their mass exchanges with oceans and the atmosphere are still subject to considerable uncertainties. Compared to sediment transport in rivers, this is because wind transport is not associated with a well‐identified channel network that directly links sand and dust production (source) to accumulation (sink) areas. The Lut Desert in Iran is nested in a closed topographic depression which provides an appropriate context to investigate the work of the wind. Spectacular landforms called mega‐yardangs and giant dunes are used together with modern wind data to map and quantify sandflows at different time scales. These sandflows are consistent with each other from decades to millions of years and allow to estimate the amount of sediments transported across the Lut Desert or emitted into the atmosphere. These estimates are not only important for the management of terrestrial drylands, but they can also provide information about the past evolution of planetary bodies dominated by aeolian processes such as Mars or Titan. Key Points: The wind regimes within the Lut Desert create an internal aeolian sediment‐routing system The joint development of erosional and depositional landforms are consistent with modern sandflows Source‐to‐sink aeolian fluxes are of the same order of magnitude from decades to millions of years